Influence of the Central American Seaway and Drake Passage on ocean circulation and neodymium isotopes: A model study. (18th December 2014) - Pfister, Patrik L.; Stocker, Thomas F.; Rempfer, Johannes; Ritz, Stefan P.
Abstract The sensitivity of the neodymium isotopic composition (ϵNd) to tectonic rearrangements of seaways is investigated using an Earth System Model of Intermediate Complexity. The shoaling and closure of the Central American Seaway (CAS) is simulated, as well as the opening and deepening of Drake Passage (DP). Multiple series of equilibrium simulations with various intermediate depths are performed for both seaways, providing insight into ϵNd and circulation responses to progressive throughflow evolutions. Furthermore, the sensitivity of these responses to the Atlantic Meridional Overturning Circulation (AMOC) and the neodymium boundary source is examined. Modeled ϵNd changes are compared to sediment core and ferromanganese (Fe‐Mn) crust data. The model results indicate that the North Atlantic ϵNd response to the CAS shoaling is highly dependent on the AMOC state, i.e., on the AMOC strength before the shoaling to shallow depths (preclosure). Three scenarios based on different AMOC forcings are discussed, of which the model‐data agreement favors a shallow preclosure (Miocene) AMOC (∼6 Sv). The DP opening causes a rather complex circulation response, resulting in an initial South Atlantic ϵNd decrease preceding a larger increase. This feature may be specific to our model setup, which induces a vigorous CAS throughflow that is strongly anticorrelated to the DP throughflow. In freshwater experiments following the DP deepening, ODP Site 1090 is mainly influenced by AMOC and DP throughflow changes, while ODP Site 689 is more strongly influenced by Southern Ocean Meridional Overturning Circulation and CAS throughflow changes. The boundary source uncertainty is largest for shallow seaways and at shallow sites.